A German doctor in the Andes: The medico-social vision of Maxime Kuczynski-Godard - Cueto, Marcos (2000)
For most of the 20th century, Western medicine and public health in Peru were concentrated on the coast, in the cities, and, above all, in Lima. According to an estimate made in the mid-1940s, there were approximately 1,450 doctors in Peru, of which 800 worked in Lima and Callao and, in contrast, only 650 resided in the provinces. This calculation also estimated the unequal distribution of resources that resulted from these figures: while in Lima what was then the international ideal was met, one doctor per thousand inhabitants, in the provinces the ratio was one to 8,000 inhabitants.